Metacinema as authorial enunciation: a taxonomy of hybrid films - Chinita, Fátima (2022)
Erratum: The published version contains the following typos. • Section “Self-Reflexivity as the Height of Metacinema”, paragraph 22: please read ‘metacinematic reflexivity’, ‘I make no distinction’, and ‘metafilms’ • Section “An Enunciative Taxonomy of Hybrid Metafilms”, paragraph 24: please read ‘the importance creators have’; paragraph 27, please read ‘analogical photography’; paragraph 29, please read ‘does not originate the same way’; paragraph 31, please read ‘proves to be too violent’; paragraph 32, please read ‘intradiegetic’; paragraph 36, please read ‘photogram’ (twice), ‘addresses…to’